2015
DOI: 10.4254/wjh.v7.i10.1403
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in the immunohistochemical evaluation of liver tumors

Abstract: Immunohistochemistry often plays an important role in the evaluation of liver tumors. Recent advances have established a classification system for hepatocellular adenomas (HCAs) based on morphology, molecular alterations, and immunohistochemistry. Specifically, loss of liver fatty acid binding protein is seen in HNF1α-inactivated HCA, staining with serum amyloid A is seen in inflammatory HCA, and diffuse staining with glutamine synthetase (GS) is seen in β-catenin activated HCA. A panel of immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…However, at present, there is still lack of sensitive and special molecular markers available for the differential diagnosis between dysplastic nodules and early HCC, although there are increasing biomarker panels waiting for multi-centric validations (Table 1). Comparatively, there are a few proposed immunohistochemical markers, such as glypican-3 (GPC-3), heat-shock protein-70 (HSP-70), glutamine synthetase (GS), CD34 and sulfite oxidase (SUOX), which might help to distinguish above two entities [49,50].…”
Section: Molecular Evaluation Of Precancerous Lesionsmentioning
confidence: 99%
“…However, at present, there is still lack of sensitive and special molecular markers available for the differential diagnosis between dysplastic nodules and early HCC, although there are increasing biomarker panels waiting for multi-centric validations (Table 1). Comparatively, there are a few proposed immunohistochemical markers, such as glypican-3 (GPC-3), heat-shock protein-70 (HSP-70), glutamine synthetase (GS), CD34 and sulfite oxidase (SUOX), which might help to distinguish above two entities [49,50].…”
Section: Molecular Evaluation Of Precancerous Lesionsmentioning
confidence: 99%
“…Therefore, a well differentiated HCC recapitulates benign liver tissue, mimicking the following benign and pre-neoplastic entities: hepatocellular adenoma, focal nodular hyperplasia (FNH), regenerative nodule, and dysplastic nodule in cirrhotic liver. In order to demonstrate malignancy in a well-differentiated HCC that morphologically resembles benign hepatocytic lesions, IHC such as CD34 (showing diffuse sinusoidal capillarization), and a panel of glutamine synthetase (GS), glypican-3 (GPC-3) and heat shock protein 70 (HSP-70) may be helpful[4,5]. Reticulin special stain remains a very useful test, as the aforementioned benign and pre-neoplastic entities generally retain a reticulin network, whereas HCC does not.…”
Section: Role Of Immunohistochemistry In Hepatocellular Carcinoma Diamentioning
confidence: 99%
“…While it would be relatively straightforward to document malignancy based on histomorphology, documenting that the tumor demonstrates immuno-histochemical evidence of hepatocellular phenotype, and excluding other lines of differentiation are necessary in arriving at the correct diagnosis of HCC. Several immuno-histochemical markers including hepatocyte in paraffin 1 (HepPar1), Arginase-1, CD10, polyclonal carcinoembryonic antigen, bile salt export pump and GPC-3 have been utilized in this setting with variable sensitivities and specificities depending on the degree of differentiation of HCC[3,4,7,8]. One study suggested that a combination of Arginase 1 and GPC-3 has the highest sensitivity in determining a hepatocellular origin of a poorly differentiated carcinoma[9].…”
Section: Role Of Immunohistochemistry In Hepatocellular Carcinoma Diamentioning
confidence: 99%
“…To determine malignancy in a well-differentiated HCC that morphologically resembles benign hepatocytic lesions, immunohistochemical staining for CD34 (showing diffuse sinusoidal capillarization), and a panel of glutamine synthetase (GS), glypican-3 (GPC-3), and heat shock protein 70 (HSP-70) can be used. [ 102 103 ] Both, the International Consensus Group of Hepatocellular Neoplasia and the WHO have adopted this three-marker panel in their recommendations. [ 104 ] In addition to this, reticulin special stains can be useful, as the aforementioned benign and pre-neoplastic entities generally retain a reticulin network, while this is not the case for HCC.…”
Section: Diagnosismentioning
confidence: 99%